2007
DOI: 10.1177/0363546507302218
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Clinical Results of Arthroscopic Single-Row and Double-Row Suture Anchor Repair for Rotator Cuff Tears

Abstract: Single- and double-row techniques provide comparable clinical outcome at 2 years. A double-row technique produces a mechanically superior construct compared with the single-row method in restoring the anatomical footprint of the rotator cuff, but these mechanical advantages do not translate into superior clinical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
311
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 395 publications
(336 citation statements)
references
References 20 publications
(39 reference statements)
14
311
0
11
Order By: Relevance
“…One reason for this can be that MRI over-estimates cuff defects [8]: we ignored many signal intensity alterations frequently seen after repair [20], considering a re-tear only when the tendon was missing and could not be visualised [21]. In line with previous studies [22], these patients were not symptomatic and had returned to their daily activity. At the last follow-up, we recorded significantly increased ROM measures in all planes, with no pain, and ASES and Constant scores were comparably improved in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this can be that MRI over-estimates cuff defects [8]: we ignored many signal intensity alterations frequently seen after repair [20], considering a re-tear only when the tendon was missing and could not be visualised [21]. In line with previous studies [22], these patients were not symptomatic and had returned to their daily activity. At the last follow-up, we recorded significantly increased ROM measures in all planes, with no pain, and ASES and Constant scores were comparably improved in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy remains as to which repair technique provides the best clinical outcome as determined by measures of patient pain and shoulder function. Multiple reviews of SR: DR repairs have concluded that there is no significant difference between SR and DR repairs based on patient outcomes [2][3][4][5][6][7][8]. In contrast, recent studies conclude double row RC repairs result in improved footplate restoration with greater coverage, fewer RC retears thereby reducing revision surgeries, and an increased ultimate load to failure.…”
Section: Introductionmentioning
confidence: 99%
“…53 Recent limited prospective studies have shown equivalent clinical results, with no significant difference in postoperative healing, although the power of the studies is limited. 22,53 With the advent of these new techniques, the postoperative rehabilitation may be slightly accelerated to maintain a careful balance between healing and minimization of postoperative stiffness. 16,22,38,67 H istorically, the management of massive rotator cuff tears included a wide range of procedures, including open or arthroscopic debridement, repair (complete or partial), and muscle or tendon transfer (upper portion of the subscapularis, latissimus dorsi, pectoralis major, tendon allografts, synthetic graft material, and xenograft).…”
mentioning
confidence: 99%
“…22,53 With the advent of these new techniques, the postoperative rehabilitation may be slightly accelerated to maintain a careful balance between healing and minimization of postoperative stiffness. 16,22,38,67 H istorically, the management of massive rotator cuff tears included a wide range of procedures, including open or arthroscopic debridement, repair (complete or partial), and muscle or tendon transfer (upper portion of the subscapularis, latissimus dorsi, pectoralis major, tendon allografts, synthetic graft material, and xenograft). 1,2,11,23,50 Although repair is always preferred, it is technically more difficult and associated with a higher incidence of failure.…”
mentioning
confidence: 99%